2016
DOI: 10.1038/srep30579
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ferroelectric contributions to electromechanical response by frequency dependent piezoresponse force microscopy

Abstract: Hysteresis loop analysis via piezoresponse force microscopy (PFM) is typically performed to probe the existence of ferroelectricity at the nanoscale. However, such an approach is rather complex in accurately determining the pure contribution of ferroelectricity to the PFM. Here, we suggest a facile method to discriminate the ferroelectric effect from the electromechanical (EM) response through the use of frequency dependent ac amplitude sweep with combination of hysteresis loops in PFM. Our combined study thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 49 publications
0
42
0
Order By: Relevance
“…Reprinted from Strelcov et al 334 with the permission of AIP Publishing. Another method to determine whether a material is piezoelectric is to determine the frequency dispersion, as shown by Seol et al 336 Reproduced from Seol et al 336 . A similar example is indicated by Chen et al 118 (e-h) Comparison of soda-lime glass (e,f) and PZT sample (g,h) hysteresis loops as a function of voltage window and frequency of the applied DC switching waveform.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reprinted from Strelcov et al 334 with the permission of AIP Publishing. Another method to determine whether a material is piezoelectric is to determine the frequency dispersion, as shown by Seol et al 336 Reproduced from Seol et al 336 . A similar example is indicated by Chen et al 118 (e-h) Comparison of soda-lime glass (e,f) and PZT sample (g,h) hysteresis loops as a function of voltage window and frequency of the applied DC switching waveform.…”
Section: Resultsmentioning
confidence: 99%
“…This technique is shown in Figure 10 (a,b). 335 Alternatively, one can also explore the frequency dependence of the signal, a technique explored recently by Kim et al 336 Here, the authors exploit the fact that across a frequency range of a few hundred kHz, the (intrinsic) piezoelectric properties of ferroelectrics are not heavily dependent on the probing frequency, whereas they are likely heavily frequency dependent for ionic redistribution. The surface displacement induced by ionic motion can be modeled as process is contributing to the observed electromechanical response.…”
Section: Via Means To Distinguish Piezoelectric From Non-piezoelectmentioning
confidence: 99%
“…For instance, Seol et al reported that it is two orders of magnitudes smaller than the electrochemical strain. [112] However, flexoelectricity is still poorly understood and, furthermore, its contribution cannot be clearly discriminated from the ionically induced chemical effect, e.g., the electrochemical strain. [114] Further investigation will be necessary to clarify the contribution of the flexoelectricity to the observed PFM response explicitly.…”
Section: Electrochemical Strainmentioning
confidence: 99%
“…In order to differentiate a ferroelectric contribution from the EM response, several approaches have been suggested, based on observed variations in the EM response due to experimental conditions. [96,97,112] We here introduce several approaches that can be readily implemented using PFM. frequency-dependent amplitude sweep was employed, as schematically depicted in Fig.…”
Section: Differentiation Of the Ferroelectric Contribution From The Ementioning
confidence: 99%
See 1 more Smart Citation